La ineficiente implementación de la carrera administrativa en Colombia desde la Constitución de 1991 (2019)
The present work presents an analysis of the reasons why the principles of the administrative career in Colombia have not been developed and institutionalized in such a way as to allow an adequate functioning of the system. The institutionalization of the principles of the administrative career has had multiple attempts at sabotage mainly by legislators. These facts show a close relationship with corruption phenomena over time, where specific groups of the population have been benefited through legislation. This work begins with a brief contextualization of what has happened with the legislation that develops the administrative career, emphasizing the progress it has had after the Political Constitution. Then, there is an analysis of the role played by organizations such as the Constitutional Court and the State Council in defending the principles that govern the administrative career. Finally, there is an analysis of the way how the figure of provisionality is being used to link people to career positions, evading the principles of merit and equality, going beyond even the constitutional duty to motivate administrative acts and the right to due process, since provisional employees are being indiscriminately disengagement.